Bio-inspired Transparent Microfluidic Platform as Transformable Networks for Solar Modulation - E., Alston, Mark; Pottgiesser, Uta; Knaack, Ulrich
The glazed envelopes on buildings play a major role in operational energy consumption as they define the boundary conditions between climate and thermal comfort. Such a facade is viewed as an uncontrolled load that sets the operational performance requirements for artificial lighting and air-cooling mechanical systems. This is in contrast to nature, which has evolved materials with the ability to learn and adapt to a micro-environment through selfregulation using materials that are multifunctional, formed by chemical composition in response to solar load. Leaf vasculature formations are of particular interest to this paper. Through leaf maximisation of daylight capture, the total leaf area density and angular distribution of leaf surfaces define the tree structure.This paper will define an approach to simulate nature to advance a microfluidic platform as a dynamic NIR absorber for solar modulation:a transformable network of multi-microchannel geometry matrix structures for autonomous transparent surfaces, for real timeflow management of conductivity. This is realised through active volumetric flows within a capillary network of circulation fluidicswithin it, through it, and out of it for energy capture and storage, the cycle of which is determined through precise management of heatflow transport within a material. This advances transparent facades into an energy system for heat load modulation nested to climateand solar exposure, which is demonstrated in this paper.